Bond strength of reinforcing bars in ultra-high performance concrete: Experimental study and fiber–matrix discrete model. (1st December 2021) - Qi, Jianan; Cheng, Zhao; John Ma, Zhongguo; Wang, Jingquan; Liu, Jiaping
Highlights: 96 samples were tested to investigate the bond behavior of reinforcing bars in UHPC. The minimum development lengths for different concrete cover were recommended. A theoretical bond strength model using fiber–matrix discrete concept was proposed. The proposed model was in good agreement with 343 test data collected from literature. Abstract: The study provided an experimental and theoretical investigation on the bond behavior of reinforcing bars in ultra-high performance concrete (UHPC) via a series of pullout tests. Test parameters included depth of concrete cover, bar embedment length and bar diameter. Failure mode, crack pattern and load-slip response were recorded and discussed under different test parameters. Test results indicated that inadequate concrete cover depth led to splitting failure while short embedment length resulted in concrete cone failure, corresponding to lower bond strengths. The bond strength increased up to 229.8% and the pullout energy increased 401.4% as the concrete cover depth increased from 0.5 d to 2 d . The development lengths were recommended to be 6 d and 8 d corresponding to the concrete cover depth of 2 d, 1.5 d, respectively. A theoretical bond strength model using fiber–matrix discrete concept was proposed and validated by comparing the calculated values with the test results and 343 test data collected from literature. The average ratios of the calculated results to the test results and collected data were 0.996 and 1.039, with a standard deviation of 0.255 and 0.252. The proposed model established the connection between the meso -scale bond property of fibers and matrix and the macro-scale bond strength of steel bars and UHPC, offering an alternative perspective in understanding the bond performance of steel bars in UHPC.